Nanogels as Next Generation Drug Delivery Systems - Sri Sruthi K; Satya Lakshmi S; Srinivasa Rao Y; Kamala Kumari P.V (Journal of Global Pharma Technology, 2020)
Nanogels are the innovative drug delivery systems which plays an integral part in pointing out many issues related to old and modern courses of treatment, such as nonspecific effects and poor stability. Nanogels are the highly cross linked nanosized hydrogels ranges from 20-200 nm. These can also be administered through various routes, including oral, pulmonary, nasal, parenteral, intraocular etc. Nanogels have high degree of drug loading capacity and it also shows better permeation capabilities due to a smaller size. These are also release the drug by pH responsive, thermosensitive, volume transition, photochemical internalization and photo-isomerization mechanism.Withemerging field of polymer sciences it has now become an inevitable to prepare smart nanosystems which can prove effective for treatment as well asclinical trials progress. The present review providing the comprehensive illustrations on novel applications, drug loading technique, mechanism of the drug release from nanogels. Further, current status, clinical trial status, and future perspective of the nanogels have been summarized.